Analysis of different injuries of basketball players based on surface electromyography - Lv, S.; Dong, Y. (Revista Brasileira de Medicina do Esporte, 2021)
Assessing the performance of basketball players is very important in the implementation of technical training programs. The application of electromyography (EMG) in basketball players is still relatively small. The evaluation of athletes` muscle state index by EMG can guide sports training. This study used surface electromyography to test and compare EMG data, analyze muscle discharge timing, contribution rate and integral EMG value of the turning movement, aiming to explore the prevention mechanism of different types of injury affecting basketball players. The synchronous measurement model of EMG signal and plantar pressure curve in jump shot process of basketball players is established to deepen coaches` understanding of jump shot movement rules and guide athletes to conduct scientific jump shot training. The research shows that the incidence of knee joint injury is relatively high in basketball players. Patella strain and softening, knee meniscus injury and cruciate ligament injury are the main types of injury, and there is no difference between genders.